A new label-free and turn-on fluorescence probe for hydrogen peroxide and glucose detection based on DNA–silver nanoclusters1. Issue 19 (7th October 2015) - Han, Hui-Xia; Tian, Xue; Kong, Xiang-Juan; Yu, Ru-Qin; Chu, Xia
<x xml:space="preserve">Abstract</x> A label-free and turn-on strategy for H2O2 and glucose detection based on the cleavage of ssDNA by ˙OH and the fluorescence enhancement effect when guanine-rich (G-rich) DNA sequences are in proximity to DNA–silver nanoclusters (DNA–Ag NCs).